The Effectiveness of Reflective-Intuitive Al Fatihah Reading Therapy in Reducing Autoimmune Survivor Stress - Muhammad Fauzan Elka Putra; Fuad Nashori (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study aims to investigate the employment of a reflective-intuitive reading of the Al Fatihah chapter as a therapy to decrease stress levels in patients with autoimmune. Conducting experimental research, the research design of this study is a non-randomized pretest-posttest control group and the participant recruited are female Muslims suffering from one of the autoimmune diseases. In this research, to measure stress levels, this study adapts a stress subtest of the Depression Anxiety Stress Scale (DASS) in which the Indonesian language is used to administer the scale. The therapy itself adopts Maulana, Subandi, and Asturi’s (2016) module of a reflective-intuitive reading of the Al Fatihah chapter. The data are analyzed through the Mann-Whitney U-Test in order to figure out the differences of the levels of stress in the experimental group before and after the intervention given and afterward to compare it to the control group. This study reveals the meaning process in the reflective-intuitive reading of the Al Fatihah for a particular time could decrease the levels of stress of patients with an autoimmune disease. Penelitian ini bertujuan untuk mengkaji peran terapi membaca Al Fatihah reflektif-intuitif dalam penurunan tingkat stres pada pasien autoimun. Penelitian ini menggunakan metode eksperimen kuasi dengan desain non-randomized pretest-posttest control group design. Subjek yang dilibatkan dalam penelitian ini adalah perempuan yang beragama Islam dan menderita salah satu penyakit autoimun. Dalam penelitian ini tingkat stres subjek diukur menggunakan Depression Anxiety Stress Scale (DASS) subtes stres yang sudah diadaptasi ke dalam bahasa Indonesia. Pelaksanaan terapi mengacu pada modul membaca Al Fatihah reflektif-intuitif yang dikembangkan peneliti dan tim dengan merujuk pada modul Maulana, Subandi, dan Asturi. Analisis data menggunakan uji Mann Whitney U-Test untuk mengetahui perbedaan tingkat stres pada kelompok perlakuan di saat sebelum dan sesudah intervensi dibandingkan dengan kelompok kontrol. Hasil penelitian menunjukkan bahwa terapi membaca Al Fatihah reflektif-intuitif dapat menurunkan tingkat stres pada pasien autoimun setelah melewati proses pemaknaan yang menghabiskan waktu tertentu.